TVET Students' Readiness for Shariah-Compliant Careers: An Analysis of Awareness, Skills, and Attitudes in the Halal Sector - Ismail Sazemi, Nuramira; Sulong , Muhammad Suhaimi (Journal of Quranic Sciences and Research, 2026)
The halal industry is one of the fastest-growing sectors globally, requiring a competent, skilled workforce deeply grounded in Shariah compliance. However, the readiness of technical and vocational education and training (TVET) students to bridge the gap between technical skills and Islamic ethical demands has not been comprehensively explored. Therefore, this study was conducted to assess the levels of awareness, practical skills, and attitudes of TVET students towards Shariah-compliant careers in the halal industry, identify differences by gender, and analyze the relationships among these three variables. This study employed a quantitative, survey-based approach. A total of 210 third- and fourth-year students from five TVET programs across four faculties at Universiti Tun Hussein Onn Malaysia (UTHM) were selected using stratified random sampling. The research instrument was a structured questionnaire, and the data were analyzed using descriptive and inferential statistics (T-Tests and Pearson's correlation). The results indicated that students’ levels of awareness, skills, and attitudes toward the halal sector were high, with a notably strong positive alignment regarding the spiritual and moral significance of halal career pathways. No significant gender differences were found across the three constructs (p > 0.05). The findings also revealed significant, strong, positive relationships among awareness, skills, and attitudes (p < 0.01). In conclusion, TVET students have strong potential to fill the workforce gap in this industry as ethically responsible, technically competent human capital. The findings provide important implications for integrating Quranic imperatives and Shariah compliance within TVET curriculum development, halal employment policies, and national strategic initiatives.